Quantitative determination of hyrdoxycinnamic acids of portulaca oleracea herb - Kinichenko, A. O.; Trzhetsynskyi, S. D.; Кініченко, Анна Олександрівна; Тржецинський, Сергій Дмитрович (Запорізький державний медичний університет, 2018)
Introduction. Hydroxycinnamic acids have antiviral, anti-inflamatory, immunostimulatory and antioxidant activities. Also, hydroxycinnamic acids can contribute to the pharmacological effects of Portulaca oleracea. Standardization and quality control of new medicinal plants are important aspects in providing efficacy and safety of finished phytopreparations which created on its basis. The aim of our work was to study the total content of hydroxycinnamic acids of Portulaca oleracea herb.
Keywords: тези доповідей